Three-dimensional crossbar arrays of self-rectifying Si/SiO2/Si memristors - Can Li (Nature Portfolio, 2017)
Memristors are key structural units of complex memory and computing systems, yet most currently available memristors are based on materials that are not compatible with silicon technology. Here, the authors demonstrate a CMOS-compatible, self-rectifying memristor and arrays entirely based on p-Si/SiO2/n-Si.